Paradigma Baru Psikologi Pendidikan Islam: Integrasi Nilai-Nilai Psikologi Islam dalam Proses Pendidikan Islam - sigit purnomo; Muhammad Fikrun Najib; Dede Rubai Misbahul (CV. ITTC INDONESIA, 2026)
This article discusses the new paradigm of Islamic educational psychology through the integration of Islamic psychological values into the process of Islamic education. This study is motivated by the dominance of the Western educational psychology paradigm, which is secular-positivistic in nature and tends to neglect the spiritual dimension of human beings, thereby creating a gap with the transcendent objectives of Islamic education, amid the growing moral crisis and character degradation among young generations due to digitalization. This research employs a qualitative approach through a library research method with content analysis applied to various relevant literature and scientific journal articles. The findings reveal that Islamic psychology is built upon five interrelated fundamental elements of the human being, namely fitrah, nafs, qalb, aql, and ruh, which are epistemologically distinct from conventional Western psychology. This distinction drives a paradigm shift toward Islamic educational psychology, manifested through various concrete forms of integration in the learning process, such as tarbiyah al-qalb (heart education), moral character formation, the strengthening of learning motivation based on sincere intention (ikhlas), and the exemplary teaching method (uswah hasanah). The implementation of this paradigm brings significant implications for students' character formation, including the strengthening of emotional intelligence, the achievement of holistic mental health, the formation of an insan kamil (perfect human) personality, and readiness to face contemporary educational challenges. This study recommends that Islamic educational institutions develop learning models that consistently integrate Islamic psychological values in order to produce a generation that is balanced in intellectual intelligence, emotional maturity, and spiritual depth.